Analisis Strategi Pemasaran dalam Meningkatkan Jumlah Kepesertaan Bukan Penerima Upah di BPJS Ketenagakerjaan Cabang Gorontalo - Wantu, Mia Arista B.; Wolok, Tineke; Ismail, Yulinda (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Mia Arista B. Wantu, 2024. "Marketing Strategy Analysis in Increasing the Number of Non-Wage Earner Participants in BPJS Employment Gorontalo Branch" Undergraduate Management study program, Faculty of Economics and Business, Gorontalo State University, Supervisor I Mrs. Dr. Tineke Wolok, S.T, M.M and Supervisor II Mrs. Yulinda L. Ismail M.si According to Employment Law No. 24 of 2011 concerning Social Security Administering Bodies which states that: all workers in Indonesia are required to register themselves as BPJS Employment participants for six months. BPJS Employment (Social Security Administering Body) is a public program that provides protection to workers to overcome certain socio-economic risks and its implementation uses sharia mechanisms. This research uses a descriptive qualitative research method with the focus of the research being (1) What are the marketing strategies carried out by the Gorontalo branch of BPJS Employment to increase the number of non-wage earners? and (2) What are the efforts of BPJS Employment Gorontalo Branch to ensure that BPU membership remains active in BPJS Employment Gorontalo? The results of this research are (1) The marketing strategy to increase the number of Non-Wage Earner participants used by BPJS Employment Gorontalo branch uses the Marketing Mix: product, price, people, and process (2) Efforts made by BPJS Employment to ensure membership remains active are marketing communication strategies and customer satisfaction strategies.